MANAJEMEN REKRUTMEN TENAGA PENDIDIK DI MTs DARUSSALAM MUARA TEMBESI - Ririn Fadillah; Mahmud MY; Riftiyanti Savitri (JMiE (Journal of Management in Education), 2020)
This research aims to describe the management of recruitment of educators in MTs Darussalam Muara Tembesi. This study uses qualitative methods. Data collection techniques using observations, interviews, and documentation. The results showed that the procurement of well-managed education personnel includes several activities, first, establishing the number of teachers needed. Second, the determination of quality and placement of teachers according to the needs based on job description and job specification. Third, determine the number of teachers received according to the needs of madrasah based on the right man in the right place and the right man in the right job. Fourth, establish teacher welfare and career development so that teachers are always motivated to improve their skills in academic and non-academic fields. A well-managed recruitment process can produce qualified human resources in MTs Darussalam Muara Tembesi.